International and Domestic Graduate Student Satisfaction with Life: Application of the Perfectionism Diathesis-Stress Model - Suh, Hanna; Hong, Jihee; Rice, Kenneth; Kelly, Victoria (Journal of International Students, 2021)
With increasing mental health problems witnessed among students, adequately addressing their well-being is becoming important on college campuses. This study compares international and domestic graduate students in the United States on domains that are relevant to both student groups (perfectionistic personality, academic stress) and how these factors combinedly predict satisfaction with life. With 531 international and 359 domestic graduate students, results found support for perfectionism and academic stress predicting life satisfaction in both groups with notable similarities and differences. For perfectionists in both student groups, the level of academic stress was an important factor that determined satisfaction with life. Interestingly, for international students only, the perfectionism dimension of standards, which has been traditionally considered adaptive, functioned in a maladaptive way. Findings from this study suggest that international and domestic students share similarities and differences that should be noted.